On interaction of an elastic wall with a Poiseuille type flow - Chueshov, I.; Ryzhkova, I. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study dynamics of a coupled system consisting of the $3D$ Navier-Stokes equations which is linearized near a certain Poiseuille type flow in an (unbounded) domain and a classical (possibly nonlinear) elastic plate equation for transversal displacement on a flexible flat part of the boundary. We first show that this problem generates an evolution semigroup $S_t$ on an appropriate phase space. Then under some conditions concerning the underlying (Poiseuille type) flow we prove the existence of a compact finite-dimensional global attractor for this semigroup and also show that $S_t$ is an exponentially stable $C_0$-semigroup of linear operators in the fully linear case. Since we do not assume any kind of mechanical damping in the plate component, this means that dissipation of the energy in the fluid flow due to viscosity is sufficient to stabilize the system.